Estudio de la aplicación de biofertilizantes orgánicos en el desarrollo agronómico del cultivo de pimiento (Capsicum annum L.) en la zona de Mocache, Ecuador durante la época seca del año 2013. - Hidalgo Franco, Angel Vicente (2015)
The overall objective of the research was to assess the implementation of the broth Worm compost, biofertilizers goat urine and manure you three high doses 100, 75 and low average 50 liters per hectare in the cultivation of pepper (Capsicum annuum L .) Mocache area in the province of Los Ríos it held at the experimental farm of Maria Quevedo State Technical University which is located at kilometer 7.1 / 2 pathway Quevedo - El Empalme, Province Los Rios. The geographical location is 01 06 "South and altitude 79 29 'West longitude, located at a height of 120 meters above sea level. The agro-climatic characteristics of the area is humid tropical, annual average temperature of 24.8 ° C, annual rainfall of 2252.5 mm, relative humidity of 84% and 894.0 hours of annual average sunshine hours. The soil is clay loam, irregular topography and drainage with a pH of 5.8.....